Does increased exercise or physical activity alter ad-libitum daily energy intake or macronutrient composition in healthy adults? A systematic review. - Joseph E Donnelly; Stephen D Herrmann; Kate Lambourne; Amanda N Szabo; Jeffery J Honas; Richard A Washburn (PLoS ONE)
Background The magnitude of the negative energy balance induced by exercise may be reduced due to compensatory increases in energy intake. Objective TO ADDRESS THE QUESTION: Does increased exercise or physical activity alter ad-libitum daily energy intake or macronutrient composition in healthy adults? Data sources PubMed and Embase were searched (January 1990-January 2013) for studies that presented data on energy and/or macronutrient intake by level of exercise, physical activity or change in response to exercise. Ninety-nine articles (103 studies) were included. Study eligibility criteria Primary source articles published in English in peer-reviewed journals. Articles that presented data on energy and/or macronutrient intake by level of exercise or physical activity or changes in energy or macronutrient intake in response to acute exercise or exercise training in healthy (non-athlete) adults (mean age 18-64 years). Study appraisal and synthesis methods Articles were grouped by study design: cross-sectional, acute/short term, non-randomized, and randomized trials. Considerable heterogeneity existed within study groups for several important study parameters, therefore a meta-analysis was considered inappropriate. Results were synthesized and presented by study design. Results No effect of physical activity, exercise or exercise training on energy intake was shown in 59% of cross-sectional studies (n = 17), 69% of acute (n = 40), 50% of short-term (n = 10), 92% of non-randomized (n = 12) and 75% of randomized trials (n = 24). Ninety-four percent of acute, 57% of short-term, 100% of non-randomized and 74% of randomized trials found no effect of exercise on macronutrient intake. Forty-six percent of cross-sectional trials found lower fat intake with increased physical activity. Limitations The literature is limited by the lack of adequately powered trials of sufficient duration, which have prescribed and measured exercise energy expenditure, or employed adequate assessment methods for energy and macronutrient intake. Conclusions We found no consistent evidence that increased physical activity or exercise effects energy or macronutrient intake.